Myron Korduba: A Legacy of Ukrainian Geography - Valerii Rudenko; Kateryna Hrek; Tetiana Iemchuk; Ksenia Maryniak (trans.) (East/West: Journal of Ukrainian Studies)
This article examines the life and research activity of the distinguished Ukrainian scholar in the field of geography Myron Korduba (1876–1947). His contributions to Ukrainian geography are revealed through a survey of his work in the areas of the population geography of Ukraine; econo- and politico-geographical regional and country studies; geographical pedagogy and cartography; and historical and toponymic geography. Korduba’s geographical legacy has not been widely investigated and is not well known in Ukrainian and international scholarship and education. This is mainly owing to the fact that he is perceived primarily a historian—indeed, one who enriched Ukrainian scholarship with innovative production in the historical disciplines. Thus, those who have studied Korduba’s creative output have tended to overlook his extraordinarily significant geographical oeuvre; it has heretofore received only superficial contemporaneous and contemporary exploration. Korduba’s principles and postulations in geography are introduced into the geographical scholarly literature in a novel way. They include ideas on the space, territory, and population of Ukraine; on the Ukrainian people, state, and language; on the treatment of geographical names as a historical source; and on the gleaning of information from the names of settlements.